Linked-color imaging combined with the NICE classification system for optical diagnosis of colon polyps: new image-enhanced endoscopic technology for pathological prediction - Wu CH; Chen TH; Hsu CM; Su MY; Chiu CT; Wu RC; Lai CC (Dove Medical Press, 2017)
Chi-Huan Wu,1,2 Tsung-Hsing Chen,1–3 Chen-Ming Hsu,1,2 Ming-Yao Su,1,2 Cheng-Tang Chiu,1,2 Ren-Chin Wu,4 Cheng-Chou Lai5 1Department of Gastroenterology and Hepatology, Linkou Medical Center, Chang Gung Memorial Hospital, Taoyuan, 2Chang Gung University, College of Medicine, Taoyuan, 3Graduate Institute of Clinical Medical Sciences, Chang Gung University, Taoyuan, 4Department of Pathology, Linkou Medical Center, Chang Gung Memorial Hospital, Taoyuan, 5Department of Colon and Rectal Surgery, Linkou Medical Center, Chang Gung Memorial Hospital, Taoyuan, Taiwan Introduction: Linked-color imaging (LCI) is a recently developed system used in endoscopy. It creates clear and bright endoscopic images using short-wavelength, narrow-band laser light combined with white laser light. The illuminating light and signal processing emphasize slight color differences in abnormal regions that approximate the normal color of the mucosa. As a result, regions initially appearing red become a deeper shade of red, while regions originally appearing white become brighter, yet with natural tones. This process facilitates recognition of slight differences in the color of the mucosa and clarifies the boundaries of the mucosal pit. Aim: To determine whether LCI of the colon can improve the correlation between endoscopic findings and pathological diagnosis. Methods: Consecutive patients who underwent colonoscopy requiring polypectomy or removal by biopsy forceps if possible were recruited. Probable polyp histology was assessed by two endoscopists using the Narrow-band imaging International Colorectal Endoscopic (NICE) classification and LCI data. All detected polyps were sent to the pathology department for pathological diagnosis by two pathologists. Results: In total, 94 polyps were found in 43 patients. The sensitivity, specificity, positive predictive value, and negative predictive value for neoplastic lesion prediction (NICE type2/3) were 96.5%, 83.8%, 90.2%, and 93.9%, respectively. Conclusion: LCI combined with the NICE classification system is a powerful tool for predicting probable histology of colon polyps. Keywords: linked-color imaging, NICE classification, colon polyps, histology, sensitivity, specificity